Political Branding of Indonesian Governor in the Social Media - Indah Suryawati (MEDIALOG: Jurnal Ilmu Komunikasi, 2021)
This study aims first, to calculate the frequency of occurrence of messages and attributes that can be seen and interpreted as political branding in Ridwan Kamil, Anies Baswedan and Ganjar Pranowo's Instagram posts during the period January to March 2021; second, to see the extent to which the similarities and differences in political branding appear on Instagram posts, and third, to specifically and comprehensively interpret the political branding of Ridwan Kamil, Anies Baswedan and Ganjar Pranowo. The research method used is content analysis method using a quantitative approach. The object of this research is posting messages on the Instagram accounts of Ridwan Kamil, Anies Baswedan, and Ganjar Pranowo in January to March 2021. The results show that there are similarities in the meaning of Ridwan Kamil, Anies Baswedan and Ganjar Pranowo's political branding messages in Instagram accounts during the period January to March 2021. These three governors display their identification as figures who are close to the people, caring, assertive, open, responsive, and care about the environment. Similarities and differences can be seen in the positioning component. In an Instagram post, the three governors sided with the general public. What is even more interesting is Ganjar Pranowo's post with #LapakGanjar which emphasizes his alignment with UMKM. However, these three governors gave different values ​​to political products. Ridwan Kamil and Ganjar Pranowo prioritize performance related to improving people's welfare, while Anies Baswedan's political products are dominated by performance improvement in infrastructure development.